2005
DOI: 10.1152/ajpheart.00926.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of dual-site phospholamban phosphorylation in intermittent hypoxia-induced cardioprotection against ischemia-reperfusion injury

Abstract: . Role of dual-site phospholamban phosphorylation in intermittent hypoxia-induced cardioprotection against ischemia-reperfusion injury. Am J Physiol Heart Circ Physiol 288: H2594 -H2602, 2005. First published January 6, 2005; doi:10.1152/ajpheart.00926.2004.-Cardioprotection by intermittent high-altitude (IHA) hypoxia against ischemia-reperfusion (I/R) injury is associated with Ca 2ϩ overload reduction. Phospholamban (PLB) phosphorylation relieves cardiac sarcoplasmic reticulum (SR) Ca 2ϩ -pump ATPase, a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…Preischemic IH adaptation for several weeks increased phospholamban phosphorylation at both sites and ameliorated SERCA dysfunction, resulting in beneficial effects on cardiac contractility and I Ca (36, 256). The loss of IH-induced protection after blockade of PKA or CaMK activity (256) suggests that these kinases are critical for the IH-induced phosphorylation of phospholamban in this model. Consistent with this possibility, a rapid increase in PKA activity following hypoxia/reoxygenation was also documented in other cell types (26, 271).…”
Section: Circulatory Systemmentioning
confidence: 81%
See 2 more Smart Citations
“…Preischemic IH adaptation for several weeks increased phospholamban phosphorylation at both sites and ameliorated SERCA dysfunction, resulting in beneficial effects on cardiac contractility and I Ca (36, 256). The loss of IH-induced protection after blockade of PKA or CaMK activity (256) suggests that these kinases are critical for the IH-induced phosphorylation of phospholamban in this model. Consistent with this possibility, a rapid increase in PKA activity following hypoxia/reoxygenation was also documented in other cell types (26, 271).…”
Section: Circulatory Systemmentioning
confidence: 81%
“…Ischemia and reperfusion decrease phospholamban phosphorylation, which contributes to diminished SERCA activity and increased [Ca 2ϩ ] i (256). Preischemic IH adaptation for several weeks increased phospholamban phosphorylation at both sites and ameliorated SERCA dysfunction, resulting in beneficial effects on cardiac contractility and I Ca (36, 256).…”
Section: Circulatory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group and others have reported that long-term IH adaptation enhances the resistance to subsequent severe hypoxia/ischemia and has fewer side effects such as right ventricular hypertrophy, compared to chronic hypoxia (Ding et al 2004;Neckar et al 2002;Xie et al 2005;Zhang et al 2000a;Zhu et al 2003). Moreover, the cardiac protective effects are maintained for several weeks (Zhang et al 2000b).…”
Section: Introductionmentioning
confidence: 90%
“…85-23, Revised 1996), and all procedures were approved by the Institutional Review Board of Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences. For IH studies, rats were exposed to a hypobaric chamber and were maintained at the equivalent of 5,000 m altitude (P B = 404 mmHg, P O2 = 84 mmHg) in daylight for one 6-h period each day for 42 days (Ding et al 2004;Dong et al 2003;Xie et al 2005;Zhu et al 2003Zhu et al , 2006. Age-matched control (normoxic) animals were kept under normoxic environments for a corresponding period.…”
Section: Animal Modelmentioning
confidence: 99%